Changes in the Library Landscape Regarding Visible Minority Librarians in Canada - Li, Yanli; Kumaran, Maha; Cho, Allan; Ly, Valentina; Fernando, Suzanne; Miller, Michael David (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2022)
Objective – As a follow-up to the first 2013 survey, the Visible Minority Librarians of Canada (ViMLoC) network conducted its second comprehensive survey in 2021. The 2021 survey gathered detailed information about the demography, education, and employment of visible minority librarians (VMLs) working in Canadian institutions. Data from the 2021 survey and the analysis presented in this paper help us better understand the current library landscape, presented alongside findings from the 2013 survey. The research results will be helpful for professional associations and library administrators to develop initiatives to support VMLs.Methods – Researchers created online survey questionnaires using Qualtrics XM in English and translated them into French. We distributed the survey invitation through relevant library association electronic mail lists and posted on ViMLoC’s website, social networking platforms, and through their electronic mail list. The survey asked if the participant was a visible minority librarian. If the response was “No,” the survey closed. Respondents indicating "Yes" were asked 36 personal and professional questions of three types: multiple-choice, yes/no, and open-ended questions.Results – One hundred and sixty-two VMLs completed the 2021 survey. Chinese remained the largest ethnic identity, but their proportion in the survey decreased from 36% in 2013 to 24% in 2021. 65% were aged between 26 and 45 years old. More than half received their library degree during the 2010s. 89% completed their library degree in Canada, a 5% increase from 2013. The majority of librarians had graduated from University of Toronto (25%), followed closely by University of British Columbia (23%), and Western University (22%). Only 3% received their library degree from a library school outside North America. 34% of librarians earned a second master’s degree and 5% had a PhD. 60% of librarians had less than 11 years of experience. Nearly half worked in academic libraries. Most were located in Ontario and British Columbia. 69% of librarians were in non-management positions with 5% being senior administrators. 25% reported a salary above $100,000. In terms of job categories, the largest group worked in Reference/Information Services (45%), followed by Instruction Services (32%), and as Liaison Librarians (31%). Those working in Acquisitions/Collection Development saw the biggest jump from 1% in 2013 to 28% in 2021. 58% of librarians sought mentoring support, of whom 54% participated in formal mentorship programs, and 48% had a visible minority mentor.Conclusion – 35% more VMLs responded to the 2021 survey compared to the 2013 survey. Changes occurred in ethnic identity, generation, where VMLs earned a Master of Library and Information Science (MLIS) or equivalent degree, library type, geographic location, and job responsibilities. The 2021 survey also explored other aspects of the VMLs not covered in the 2013 survey, such as librarian experience, salary, management positions, and mentorship experience. The findings suggested that the professional associations and library administrators would need collaborative efforts to support VMLs.